Endometriosis externa within the rectus abdominis muscle - Karaman, Hatice (Ulus Cerrahi Derg, 2014)
The presence of endometrial glands and stroma outside the uterine cavity is called “endometriosis”. Recklinghausen first defined this entity in 1896, and Sampson first named it in detail in 1921. Endometriosis is most often seen in the pelvis. Although extrapelvic endometriosis is rare, it can be seen in almost every organ. Endometriosis localized in the rectus abdominis muscle is very rare. A patient who had two previous cesarean sections presented with a 23 mm heterogeneous hypoechoic mass within the rectus abdominis muscle, approximately 1 cm superior to the Pfannenstiel incision that was diagnosed as endometriosis externa by fine-needle biopsy and excisional biopsy. Herein, we report this patient along with the literature.